1983
DOI: 10.1152/ajpgi.1983.245.4.g482
|View full text |Cite
|
Sign up to set email alerts
|

Electrical basis of contractions in the muscle layers of the pig colon

Abstract: Simultaneous in vitro measurements of electrical and mechanical activities were performed, using suction electrodes and force transducers, respectively, on longitudinal and circular muscle layers of the pig proximal colon. In addition, circular muscle strips were studied with the sucrose gap technique. Spontaneous activity was present in both preparations. In the circular muscle, slow waves with superimposed spikes occurred at a variable frequency, accompanied by phasic contractions. Longitudinal muscle prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 0 publications
1
23
0
1
Order By: Relevance
“…A 5-cm segment of proximal small intestine with the pylorus attached was excised and pinned without tension on the bottom of a 5-ml water-jacket bath coated with Sylgard (Dow Corning, Midland, MI) at 37 Ϯ 0.5°C and bathed at 2 ml/min with warmed modified Krebs solution (in mM: 125 NaCl, 5 KCl, 2.5 CaCl2, 1.2 MgCl2, 1.2 NaH 2PO4, 4 NaHCO3, 11 glucose, and 10 HEPES) aerated with 95% O 2-5% CO2. Slow-wave activity was recorded with a serosal Ag/AgCl suction electrode (6,10,16,33) 2 cm distal to the pylorus for a minimum of 15 min. The electric signal was amplified on a Duo 773 electrometer (World Precision Instruments, Sarasota, FL) and digitalized on a PC with an Acknowledge-MP100 Biopac system (World Precision Instruments).…”
Section: Animalsmentioning
confidence: 99%
“…A 5-cm segment of proximal small intestine with the pylorus attached was excised and pinned without tension on the bottom of a 5-ml water-jacket bath coated with Sylgard (Dow Corning, Midland, MI) at 37 Ϯ 0.5°C and bathed at 2 ml/min with warmed modified Krebs solution (in mM: 125 NaCl, 5 KCl, 2.5 CaCl2, 1.2 MgCl2, 1.2 NaH 2PO4, 4 NaHCO3, 11 glucose, and 10 HEPES) aerated with 95% O 2-5% CO2. Slow-wave activity was recorded with a serosal Ag/AgCl suction electrode (6,10,16,33) 2 cm distal to the pylorus for a minimum of 15 min. The electric signal was amplified on a Duo 773 electrometer (World Precision Instruments, Sarasota, FL) and digitalized on a PC with an Acknowledge-MP100 Biopac system (World Precision Instruments).…”
Section: Animalsmentioning
confidence: 99%
“…Between species the frequency of slow waves shows some variation; for example in the dog the frequency is about 5 cycles min-' (El-Sharkawy, 1983;Smith et al 1987 a, b) whereas in the pig the frequency is 0-5-3 5 cycles min-' (Huizinga et al 1983. Action potentials may or may not accompany the slow waves.…”
Section: Introductionmentioning
confidence: 99%
“…In colonic longitudinal muscle of several species including the guinea-pig, dog, pig and human, the.application of stretch appears to promote the onset of membrane potential oscillations. The onset of oscillatory activity appears to be controlled by both myogenic and neurogenic mechanisms (Biilbring, 1955;Gillespie, 1962;El-Sharkawy, 1983;Huizinga, Diamant & El-Sharkawy, 1983;Huizinga, Stern, Chow, Diamant & El-Sharkawy, 1985;Huizinga, Chow, Diamant & El-Sharkawy, 1987;Smith et al 1987 a).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the small bowel and stomach, the longitudinal and circular muscles of the colon exhibit different electrical activities (Christensen et al 1969;El-Sharkawy, 1983;Huizinga et al 1983). Circular muscle generates slow wave activity as described above, whereas longitudinal muscles of the dog and pig colon generate pre-potentials and action potentials that are not associated with slow waves but appear to be dependent on external stimuli such as stretch or acetylcholine (El-Sharkawy, 1983;Huizinga et al 1983). Christensen et al (1969) reported that the duration of spontaneous slow waves of the circular muscle of the cat colon in vitro was variable (3-19 s).…”
Section: Introductionmentioning
confidence: 99%